MARKET OVERREACTION SAHAM LQ-45 TERHADAP PENGUMUMAN ASIAN GAMES KE-18 - Tatang Ary Gumanti; Mareita Dewi Kasprianti; Ana Mufidah (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2019)
Sports events are now a big concern for management and sports tourism and have become a big business opportunity that has an impact on the economy, especially for countries that host the event. The Asian Games is one of the biggest sports events in Asia that are held every four years. Indonesia is the country chosen to host the 18th Asian Games which was announced on July 25, 2014. The purpose of this study is to analyze LQ-45 stock whether after Indonesia was announced to host the 18th Asian Games there was a market overreaction and was followed by the emergence of price reversals. The final sample of the study was 32 companies. Results showed the presence of market overreaction symptoms in the winner and loser portfolios in the period after the announcement. There has been a market overreaction in the winner and loser portfolios due to the announcement of Indonesia's determination to host the 18th Asian Games. Price reversal occurs in loser portfolios and does not occur in portfolio winners due to the announcement of Indonesia's determination to host the 18th Asian Games.